Characteristics of patients receiving ustekinumab compared with secukinumab for treatment of moderate‐to‐severe plaque psoriasis – nationwide results from the DERMBIO registry. (29th March 2017) - Egeberg, A.; Iversen, L.; Gniadecki, R.; Hvid, L.; Dam, T.N.; Bryld, L.E.; Skov, L.
Abstract: Background: While safety and efficacy of ustekinumab and secukinumab, monoclonal antibodies approved for psoriasis, are described in clinical trials, data on their real‐life application are lacking. Objective: We compared the characteristics of patients initiating first‐time treatment with secukinumab or ustekinumab. Methods: All Danish patients with moderate‐to‐severe plaque psoriasis treated with biologics are recorded in the nationwide DERMBIO registry. We compared characteristics of patients starting first‐time therapy with ustekinumab and secukinumab, respectively. Results: We identified a total of 1037 and 142 first‐time treatment series with ustekinumab and secukinumab. There was a male predominance in both groups, but patients initiating secukinumab were slightly older and with longer disease duration; in agreement with guidelines for biologic treatment in Denmark where ustekinumab has been first line for all with psoriasis without joint problems since 2012, and secukinumab first line for psoriasis with joint problems since July 2016. A total of (52.9% and 14.5%) patients receiving ustekinumab and secukinumab, respectively, were bio‐naïve. The mean dermatology life quality index score was slightly higher for ustekinumab than secukinumab (11.6 vs. 10.0; P = 0.0769); the mean Psoriasis Area and Severity Index score were significantly higher (10.4 vs. 7.3; P < 0.0001) for ustekinumab. Prevalence of joint disease was markedly lover (22.7% vs. 44.4%) among patients receiving ustekinumab. Conclusions: We found significant differences in characteristics of patients starting therapy with ustekinumab and secukinumab in a real‐life clinical setting. These findings may aid clinicians and researchers when interpreting efficacy data derived from clinical trials and biologic registries of patients with psoriasis.